Adsorption and Dilational Viscoelasticity of Saponin at the β-Pinene/Water and Air/Water Interfaces - Lin, Feng (Colloids and interfaces, 2025)
Understanding adsorption and interfacial properties of surface-active agents at interfaces is crucial to the formation and stability of colloidal systems such as emulsions and foams. In this work, interfacial tension and viscoelasticity of saponin at the β-pinene/water interface were studied using drop tensiometry and dilational rheology measurement. For comparison, saponin at the air/water interface was also evaluated. Both saponin and β-pinene are bio-based, eco-friendly, and abundant in plants, trees, and agricultural wastes. Results showed that dynamic interfacial tensions σ(t) of saponin adsorbed at β-pinene/water and air/water interfaces could be well described by the Ward and Tordai model, suggesting that the saponin adsorption kinetics at both interfaces are controlled by a kinetically limited mechanism. The equilibrium interfacial pressure πe data prior to critical micelle concentration (cmc) were adequately fitted by the Gibbs adsorption isotherm. At the β-pinene/water interface, a higher cmc and a larger area per molecule, but a lower πe, were observed compared to the air/water interface. Interestingly, the dilational moduli of saponin at β-pinene/water increased with increasing oscillating frequency, but with less significant frequency dependence than their counterparts at the air/water interface. The dilational moduli of saponin at β-pinene/water passed through a minimum with increasing saponin bulk concentration, while the air/water interface exhibited a strikingly different trend in terms of concentration dependence and a higher magnitude for the dilational moduli. The correlation between adsorption behaviors and dilational properties of saponin at the two interfaces is discussed. Fundamental knowledge gained from this study will be beneficial for the rational development of new biocompatible emulsions and foam products for more sustainable applications.